Information guided adaptation of complex biological systems - Herndon, R. Craig (Frontiers in Complex Systems, 2023)
Introduction: Functional information transmission through a complex biological system is introduced as a method for biological response (bioresponse) adaptation using qualified biological marker (biomarker) data. Methods: This information guided adaptation methodology traverses the series of complex connections, defined by disparate bioresponse and biomarkers data sets, by placing both data sets on the common platiorm defined by information. The absolute uncertainty associated with these data sets can be defined in terms of decimal digits of information. This relationship between the data’s absolute uncertainty and its information entropy is used to decompose information entropy into functional and relative uncertainty components, where the functional component quantifies the function or meaning of a data set in units of information. Results: Application of functional information to adapt patient medical treatments using the information values for the bioresponse model and the biomarker model are outlined in detail and presented tabularly. Discussion: Functional information provides a mathematical connection between a bioresponse model and a biomarker model by quantifying both data sets in the units of information and thereby providing the means to implement precision therapeutic plans by quantitatively adapting patient treatments using their biomarker measurements.